2020
DOI: 10.1111/mcn.12710
|View full text |Cite
|
Sign up to set email alerts
|

Childhood stunting and wasting in Myanmar: Key drivers and implications for policies and programmes

Abstract: Child undernutrition is a public health and development problem in Myanmar that is jeopardizing children's physical and cognitive development and the country's social and economic progress. We identified key drivers of child stunting (low height‐for‐age) and wasting (low weight‐for‐height) in a nationally representative sample ( n = 3,981) of children 0–59 months of age. The national prevalence of child stunting and wasting was 28% and 7%, respectively. Boys were more likely to be stunte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 32 publications
(36 reference statements)
3
30
0
1
Order By: Relevance
“…Although body mass index is not commonly measured throughout pregnancy in the region, in Myanmar, prevalence of maternal underweight after pregnancy was associated with 1.6 times higher risk of child wasting compared with mothers with normal nutrition status (Blankenship, Cashin, et al, 2020). Blankenship, Cashin, et al (2020) found that the mother's perceived size of the child as smaller than normal at birth was associated with 2.1 times higher risk of stunting compared with children perceived by the mother to be of normal size. The necessity of multisectoral actions to address poor nutrition practices is explored by Li, Nguyen, Wang, Mathisen, and Fang (2020) in an examination of the individual, family, community, and health facility factors associated with inadequate breastfeeding practices in China.…”
Section: Poor Maternal Nutritionmentioning
confidence: 95%
See 4 more Smart Citations
“…Although body mass index is not commonly measured throughout pregnancy in the region, in Myanmar, prevalence of maternal underweight after pregnancy was associated with 1.6 times higher risk of child wasting compared with mothers with normal nutrition status (Blankenship, Cashin, et al, 2020). Blankenship, Cashin, et al (2020) found that the mother's perceived size of the child as smaller than normal at birth was associated with 2.1 times higher risk of stunting compared with children perceived by the mother to be of normal size. The necessity of multisectoral actions to address poor nutrition practices is explored by Li, Nguyen, Wang, Mathisen, and Fang (2020) in an examination of the individual, family, community, and health facility factors associated with inadequate breastfeeding practices in China.…”
Section: Poor Maternal Nutritionmentioning
confidence: 95%
“…Poverty is likely to be significantly exacerbated by the COVID-19 pandemic particularly among vulnerable households. In this issue, nationally representative data was examined in Myanmar (Blankenship, Cashin, et al, 2020), the Marshall Islands , and Thailand (Okubo, Janmohamed, Topothai, & Blankenship, 2020)…”
Section: Key Messagesmentioning
confidence: 99%
See 3 more Smart Citations